2012
DOI: 10.1111/j.1743-6109.2012.02889.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Animal Investigation of the Effect of a Mixture of Herbal Extracts from Tribulus terrestris and Cornus officinalis on Penile Erection

Abstract: Introduction Herbal preparations have long been used as folk remedies for erectile dysfunction (ED). Aim This study examined the effects of Tribulus terrestris and Cornus officinalis extracts on relaxation of the smooth muscle of the corpus cavernosum (CC), their mechanisms of action, and the effects of oral administration of a mixture of the herbal extracts on penile erection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Tribulus terrestris extract and Cornus officinalis extract demonstrated concentration-dependent relaxation in an organ bath. In an in vivo study of the extract mixture, intracavernous pressure was improved and the cAMP pathway was significantly potentiated [ 44 ].…”
Section: Types Of Herbal Medicine Used To Treat Electile Dysfunctionmentioning
confidence: 99%
“…Tribulus terrestris extract and Cornus officinalis extract demonstrated concentration-dependent relaxation in an organ bath. In an in vivo study of the extract mixture, intracavernous pressure was improved and the cAMP pathway was significantly potentiated [ 44 ].…”
Section: Types Of Herbal Medicine Used To Treat Electile Dysfunctionmentioning
confidence: 99%
“…In order to confirm the hypothesis for the specificity of nitric oxide-dependent mechanism, they showed that the relaxation of CC strips by Tribulus terrestris was unsuppressed by pretreatment with a variety of other procontractile agents, including indomethacin, glibenclamide, 4-aminopyridine, and ormethyleneblue. Furthermore, the relaxation effect of Tribulus terrestris on corpus cavernosum correlated nicely with increased intra-cavernosal pressure in rats (n 1/4 = 8) measured after treatment with Tribulus terrestris for one month (Kam et al, 2012). Eventually, a study performed in 2014 did not find any beneficial effect of this compound as a pro-sexual drug in erectile dysfunction (Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Noteworthy is the fact that the same team's work evaluated the role of Tribulus terrestris in male infertility, yet it did not deliver significant results. In the same context, several studies demonstrated an enhancing role of Tribulus terrestris as an ingredient of an herbal mixture in erectile dysfunction (Gauthaman & Adaikan, 2005;Kam et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…T. terrestris extract, C. officinalis extract, and the mixture of both extracts showed concentration-dependent relaxation effects of the corpus cavernosum. Therefore, endothelium appears to be an important location of action of T. terrestris extract, functioning in relaxation mainly via NOS and exhibited relaxation effects mainly through cAMP and partly through cGMP [26]. …”
Section: Discussionmentioning
confidence: 99%